A Escola de Viticultura Ferreira Lapa e o associativismo regional em Torres Vedras: suas organizações e objetivos nos finais do século XIX - António Francisco Baixinho (EccoS – Revista Científica)
The intention with this article is to inform about the School of Viticulture Ferreira Lapa, its operation and organization, as well as local agricultural associations that arise almost simultaneously and in consequence of the crisis that the wine sector has gone through in the late nineteenth century. The objectives set for this research were: to spread knowledge; evoke the School of Viticulture Ferreira Lapa; understand the orga - nization of an agricultural vocational school in the late nineteenth century, understand the consequences of the phylloxera crisis; understand the consequences of associations in the agricultural education. In this research a qualitative methodology was used through the analysis, selection and processing of documents and gathering information on bib - liographic sources.